Pengaruh Citra Destinasi, Fasilitas Wisata, terhadap Kepuasan Konsumen pada Wisata Goa Gong Pacitan - Istikomah Istikomah; Achmad Djoni Sudirman; Iswati Iswati; Emilia Pranata (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to:1) determine the effect of destination imageon consumer satisfaction in Pacitan Gong Cave Tourism, 2) determine the effect of facilities on consumer satisfaction in Pacitan Gong Cave Tourism, 3) determine the effect of desination image, tourist facilities on consumer satisfaction in Pacitan Gong Cave Tourism. This study resulted that Destinatin Image (X1) has an effect on Consumer Satisfaction (Y), where the T count value is 4,079 > T table value 1,989, meaning that there is a significant effectof destination image (X1) on consumer satisfaction (Y). Tourismfacilities (X2) have an effect on consumer satisfaction (Y), where the T value us 2,913 > 1,989 meaning that there is a significant influence of tourism facilities (X2) on consumer satisfaction (Y). The F value is 94,504 which means it is positive with a significant value of 0,000 means less than 0,05. There fore, simultaneously the desination image variable and tourist facilities have a positive effect on the consumer satisfaction variable. And the last one is the test results for the value of R2 is 6,090 which means that the variables X1 and X2 are able to explain the variable Y by 69,0%.